2023
DOI: 10.1589/jpts.35.265
|View full text |Cite
|
Sign up to set email alerts
|

Validity of temporo-spatial characteristics of gait as an index for fall risk screening in community-dwelling older people

Abstract: [Purpose] This study aimed to identify kinematic gait indicators for a fall risk screening test through quantitative comparisons of gait characteristics measured using mobile inertial sensors between faller and non-faller groups in a population of community-dwelling older people. [Participants and Methods] We enrolled 50 people aged ≥65 years who used long-term care prevention services, interviewed them to determine their fall history during the past year, and divided them into faller and non-faller groups. Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Statistically significant differences were found in a few parameters when comparing between participants in the non-risk and potential risk of falling groups, including the RMS, Range, and summation of SA during S-TD, as well as the Range and SA during OLS ( Table 3 ). This study identified the risk group based on low gait speed and confirmed it with clinical tests such as the SPPB, as previously reported [ 22 , 24 , 27 , 28 ]. One potential factor could be attributed to the procedure of the data collection, which comprised ambulatory elderly participants, including those within the risk group, who retained the ability to walk independently on a daily basis.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Statistically significant differences were found in a few parameters when comparing between participants in the non-risk and potential risk of falling groups, including the RMS, Range, and summation of SA during S-TD, as well as the Range and SA during OLS ( Table 3 ). This study identified the risk group based on low gait speed and confirmed it with clinical tests such as the SPPB, as previously reported [ 22 , 24 , 27 , 28 ]. One potential factor could be attributed to the procedure of the data collection, which comprised ambulatory elderly participants, including those within the risk group, who retained the ability to walk independently on a daily basis.…”
Section: Discussionsupporting
confidence: 84%
“…Participants in the fall risk group were classified based on their gait speed of less than 1 m/s [ 22 ]. The Short Physical Performance Battery (SPPB) is an objective measurement instrument of balance, lower extremity strength, and functional capacity in older adults [ 23 ]; and the fall risk assessment test, Thai version (Thai-FRT), is composed of six factors, including history of falls, impaired balance, being female, specific medication used, impaired visual acuity and Thai style house [ 24 ], and used to differentiate among the potential risk and non-risk group. The demographic characteristics of the participants are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Among these, six studies reported the fallers' cadence was lower [25,32,39,45,68,98]. Although another 10 studies observed lower values of cadence in fallers, no statistically significant difference was yielded [30,31,36,55,61,86,89,94,100,102]. No study reported higher values of cadence in fallers.…”
Section: Cadencementioning
confidence: 97%
“…Gait speed was the parameter most analyzed, namely in 50 studies that compared fallers and non-fallers. Regarding these studies, 29 reported the fallers' gait speed was lower than nonfallers [14,23,[25][26][27][30][31][32]34,37,39,43,[48][49][50][55][56][57]60,63,68,75,84,85,91,93,98,100,102]. Although another 17 studies observed lower values of gait speed in fallers, no statistically significant differences were yielded [22,24,28,36,58,[60][61][62]66,76,[80][81][82]86,89,91,94].…”
Section: Gait Speedmentioning
confidence: 99%
“…A longitudinal study of pregnant gait biomechanics demonstrates the increased falling risk during the 3rd trimester of pregnancy associated with changes in lower extremity kinematics and foot pressure alterations [ 34 ]. The assessment of gait velocity and heel strike angle using mobile inertial sensors has been shown to be essential kinematic indicators in a fall risk screening test [ 35 ]. Biomechanical video-based analysis shows that to ensure safe motion, pregnant women should not initiate gait until reaching a stable standing position after rising [ 36 ].…”
Section: Research Gaps Addressable With Inertial Sensorsmentioning
confidence: 99%